EFEKTIVITAS LIMBAH AMPAS TEBU (Saccharum Officinarum L.) SEBAGAI ADSORBEN DENGAN METODE PIROLISIS UNTUK MENINGKATKAN KUALITAS AIR LIMBAH INDUSTRI GULA - Adila, Hifdzil; Wisnu, Wiliam; Handayani, Essa Tri; Fathin, Hafizhah Rana; Rusdianto, Andrew Setiawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2024)
Sugarcane bagasse is a by-product of the sugar industry which contains high levels of cellulose which can be used in making adsorbents. Another by-product of the sugar industry is liquid waste which contains dangerous pollutants which can damage river ecosystems, sugarcane bagasse adsorbent can be used to overcome river pollution caused by sugar industry wastewater, the process of making sugarcane bagasse adsorbent using the pyrolysis method is considered more effective because This method can convert long lignocellulosic chains into active carbon, so this research aims to determine the effectiveness of sugarcane bagasse adsorbents made using the pyrolysis method in dealing with river pollution caused by wastewater. The research method used is the gravimetric method for measuring water content and ash content, and the calculation method for measuring pH values ​​and yield. The analysis used is analysis of water content, ash content, pH and yield which will later be compared with charcoal standards according to SNI 06-4369-1995. The research results showed that the water content and ash content values ​​were 13.92% and 8.05%, which met the SNI 06-3730-1995 standard regarding activated charcoal. Apart from that, the pH value was obtained at 9.91 and the yield was 5.80%, where this value was influenced by the activation of activated charcoal and the pyrolysis process that occurred in the bagasse.